Election Officers' Health and Safety: An Occupational Risk Analysis - Yunia Dwie Nurcahyanie; Nismah Panjaitan; Olievia Prabandini Mulyana; Muhammad Teguh Yulianto (Advance Sustainable Science Engineering and Technology, 2025)
General elections are vital to democracy in Indonesia, yet the occupational health and safety (K3) of Voting Organizer Group (KPPS or election officers) officers is often overlooked. This study evaluates the impact of workload on the physiological health of election officers during the 2024 General Election using an ergonomics-based approach. Data were collected from seven KPPS members at TPS 07 Cerme Kidul, Gresik, East Java, measuring blood pressure and oxygen saturation before and after election day. The Wilcoxon Signed Rank Test revealed significant increases in blood pressure (p = 0.046) and decreases in oxygen saturation (p = 0.047) post-election. Key risk factors identified include long working hours, insufficient rest, and static positions. The study recommends interventions such as work shift rotations, extended rest periods, enhanced health screenings, and ergonomic improvements at polling stations. These measures aim to improve the health and safety of election officers, contributing to safer and more sustainable elections.